(untitled) (Tribhuvan University Journal of Microbiology, 2022)
Objectives: To determine prevalence of ESBL producing and non-producing Escherichia coli in different clinical specimens and biofilm production along with antimicrobial susceptibility pattern of the bacteria. Methods: The study was carried out in Sukraraj Tropical Infectious Disease Hospital, Teku, Kathmandu from September 2019 to February 2020. E. coli was identified by macroscopic, microscopic and biochemical characteristics. The AST was performed by Kirby Bauer’s disc diffusion method and ESBL production was detected by using Ceftriaxone disc metod. Biofilm detection of the isolates was done by TCP technique. Results: Out of 179 gram-negative isolates, 76(42.46%) were found to be E. coli. Out of 76 isolates, 22(28.95%) were ESBL producing and 54(71.05%) were ESBL non-producing. Among 22 ESBL producer, 8(36.36%) was found to be biofilm producer whereas among 54 ESBL non-producer 13(24.07%) was found to be biofilm producer. Biofilm producing ESBL producers were found to be sensitive towards Colistin (100%), Carbapenems (87.5%) and Nitrofurantoin (87.5%) whereas biofilm producing ESBL non-producer was found to be sensitive towards Colistin (100%) Carbapenems (100%) and Nitrofurantoin (100%). Conclusion: For the treatment of ESBL infection, currently carbapenems are the drug of choice. Among ESBL producers and non-ESBL producers, biofilm production was high with 36.36% in ESBL producing isolates.